Measurement of mean and turbulence flow of gas-liquid stirred tank operating at high gas flow rates - Wang, Zhi Lei; Pang, Sook Fun; Gimbun, Jolius (Elsevier Ltd, 2026)
This study investigates the hydrodynamics and power characteristics of a gas–liquid stirred tank equipped with either a long-armed pitched paddle (LAPP) impeller or a Rushton disc turbine (RDT) operating at a high gas flow rate of 1.1 VVM. The mean and turbulent flow fields were quantified using two-dimensional particle image velocimetry (PIV), while the power draw was measured with an in-line torque meter. The LAPP impeller exhibited a turbulent power number of 1.21. Under gassed conditions, the power draw was reduced by up to 60 , demonstrating a superior gas-handling capability compared to the RDT. In single-phase flow, both impellers generated a double-loop circulation pattern near the tank wall. The LAPP impeller attained maximum radial and axial velocities of approximately 0.18 Vtip and 0.25 Vtip, respectively, consistent with values typically reported for axial-flow impellers such as the PBT or Maxflo T. Under aeration, the mean and turbulent flow structures were significantly influenced by bubble-induced motion. Overall, the LAPP impeller exhibited efficient gas dispersion and low-shear mixing characteristics, confirming its suitability for high gas flow operations. © 2025 Institution of Chemical Engineers